Maternal perceptions of breastfeeding support in a birth hospital before and after designation to the Baby-Friendly Hospital Initiative: A quasi-experimental study - Lojander Jaana; Axelin Anna; Bergman Paula; Niela-Vilén Hannakaisa (ELSEVIER SCI LTD, 2022)
Objective: The purpose of this study was to examine maternal perceptions of postnatal breastfeeding support in the hospital before and after designation to the Baby-Friendly Hospital Initiative (BFHI). Further maternal and infant characteristics associated with the maternal perception of breastfeeding support were investigated. Our hypothesis was that mothers would perceive breastfeeding support more adherent to the standards of the BFHI after the hospital was designated to the BFHI compared with before.
Design: The study had a quasi-experimental non-equivalent two-group design.
Setting: The study was conducted in one postnatal ward and one neonatal intensive care unit in a public birth hospital in Finland.
Participants: Postpartum mothers giving birth in the hospital before (pre-test group, n = 162) and after (post-test group, n = 163) designation to the BFHI participated.
Intervention: The aim of the BFHI is to support and promote breastfeeding by implementing the Ten Steps to Successful Breastfeeding into routine care. Implementation in the study hospital required staff training and revision of current hospital practices, which took place during 2017-2018. The postnatal ward and neonatal intensive care unit were designated to the Baby-Friendly Hospital in February 2019.
Measurements: Maternal perceptions of postnatal breastfeeding support were measured with a 20-item questionnaire developed for this study. Items were based on maternal self-report of the breastfeeding support in the hospital. A sum variable was created to measure the maternal perception of the support (scale 1-7), and higher scores indicated perception of breastfeeding support that is more adherent to the standards of the BFHI. Descriptive statics, nonparametric statistical tests, and multiple linear regression analysis were used to analyse data.
Findings: Mothers in the post-test group (median 6.1, IQR 5.4-6.4) perceived breastfeeding support more adherent to the standards the BFHI compared with mothers in the pre-test group (median 5.0, IQR 4.25.8) (p < 0.001). Fifteen of 20 of the measured breastfeeding support practices improved after the hospital's designation to the BFHI. The largest difference between groups was observed for multipara mothers (median 4.6 vs 6.0, p < 0.001), older mothers ( > 35 years) (median 4.4 vs 5.8, p < 0.001), and mothers with a longer history of breastfeeding (6-12 months) (median 4.4 vs 6.2, p < 0.001). Before the BFHI designation, multipara mothers and mothers who gave birth to an infant with low Apgar scores ( < 7) perceived breastfeeding support less adherent to the BFHI standards than did primiparas or mothers of an infant with high Apgar scores ( >= 7). After the BFHI designation, mothers who experienced preterm birth (GA < 37 weeks) perceived breastfeeding support less adherent to the BFHI standards compared with mothers who experienced a full-term birth.
Key conclusions: Designation to the BFHI had a positive impact on breastfeeding support from the maternal perspective. Designation improved particularly multiparas' perceptions of receiving breastfeeding support that is in adherence with the standards of the BFHI. However, more emphasis should be placed, and further research should be conducted to ensure that mothers giving birth to a preterm infant receive breastfeeding support that is adherent to the BFHI standards.
Implications for practice: Birth hospitals are recommended to implement the BFHI as it improves breastfeeding support in the hospital and provides mothers with a good basis and continuation for breastfeeding, even after hospital discharge. Maternal perceptions about the impact of BFHI designation are important to consider because mother - infant dyads are at the centre of that support, and their viewpoint may help to assess whether the designation to the BFHI in the unit is successful. Results of this study indicate that designation to BFHI improves breastfeeding support from the maternal perspective.
(c) 2022 The Author(s). Published by Elsevier Ltd. This is an open access article under the CC BY license ( http://creativecommons.org/licenses/by/4.0/ )